The Impact Of Tax Increases, Inflation, and Government Capital Expenditure On Growth The Economy in Indonesia From The Year 2006 Until 2021 - Shofi Ana Romadhini; Sugeng Hadi Utomo (Universitas Muhammadiyah Makassar, 2022)
Economic growth is the development of activities in the economy that can increase people's prosperity and lead to sustainable economic development in a country. Tax revenue is one of the factors that is positively related to economic growth. While the components of capital expenditure and inflation are factors that can affect tax revenue. This study aims to determine the impact of tax increases, inflation, and capital expenditures on economic growth. The research approach used in this research is quantitative research with a cross-sectional design. The data used in this study is secondary data in the form of tax data, capital expenditures, and inflation for 2006-2021. The data analysis technique used in this study is multiple linear regression analysis with the SPSS 24.0 program analysis tool. The results of this study indicate that the tax and capital expenditure variables have a significant positive relationship and influence on economic growth, while the inflation variable has no significant effect on economic growth